Percent tissue altered and corneal ectasia. Issue 4 (July 2016) - Santhiago, Marcony R.
Abstract : Purpose of review: This article reviews the association of a novel metric, percentage tissue altered (PTA), with the occurrence of ectasia after laser in-situ keratomileusis in eyes with normal corneal topography, and analyses the influence of the variables that comprise it, and its role on eyes with suspicious topography. Recent findings: PTA is derived from [PTA = (FT + AD)/CCT] where FT = flap thickness, AD = ablation depth, and CCT = preoperative central corneal thickness. Our studies revealed that there is a robust relationship between high PTA and ectasia risk in eyes with normal preoperative topography. PTA higher or equal to 40% presented the highest odds ratio and highest predictive capabilities for ectasia risk than each of the variables that comprise it, residual stromal bed or age. Average thicker flaps alone were insufficient to create ectasia unless coupled with greater ablation depths, meaning a high PTA. In eyes with suspicious topography, even low PTA value is sufficient to induce ectasia. Summary: This new metric, PTA, should be taken into account when screening patients for refractive surgery. Patients with normal topography or tomography, presenting a PTA higher or equal to 40% should be considered at higher risk for post laser in-situ keratomileusis ectasia.